2018
DOI: 10.1371/journal.pone.0191606
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Circulating markers of fibrosis are associated with immune reconstitution status in HIV-infected men

Abstract: IntroductionLymphoid tissue fibrosis may contribute to incomplete immune reconstitution on antiretroviral therapy (ART) via local CD4+ T lymphocyte (CD4) depletion. Hyaluronic acid (HA) increases with fibrotic burden. CXCL4 concentrations increase in response to pro-fibrotic stimuli, but lower CXCL4 concentrations in HIV-infected individuals may reflect successful immune evasion by HIV. We investigated relationships between circulating HA and CXCL4 concentrations and immune reconstitution on ART in HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A previous study reported that caveolin-1 overexpression is associated with structural modifications of endothelial cells in patients with diabetic lung disease, indicating the potential application of caveolin-1 as a diagnostic biomarker for diabetic lung disease (16). The development of human disease is usually associated with changes in certain substances in the blood, and the detection of those substances may provide guidance for disease diagnosis (17). In the current study, the relative expression levels of SCAL1 were significantly downregulated in patients with diabetic lung disease, and downregulated serum expression levels of SCAL1 effectively distinguished diabetic patients with diabetic lung disease from diabetic patients without lung disease and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that caveolin-1 overexpression is associated with structural modifications of endothelial cells in patients with diabetic lung disease, indicating the potential application of caveolin-1 as a diagnostic biomarker for diabetic lung disease (16). The development of human disease is usually associated with changes in certain substances in the blood, and the detection of those substances may provide guidance for disease diagnosis (17). In the current study, the relative expression levels of SCAL1 were significantly downregulated in patients with diabetic lung disease, and downregulated serum expression levels of SCAL1 effectively distinguished diabetic patients with diabetic lung disease from diabetic patients without lung disease and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In paired pre/post-treatment samples, there was a tremendous increase in HA and a more significant decrease in CXCL4 in INRs, compared with UCs. It is hypothesized that increased circulating HA and lower circulating CXCL4 concentrations due to lymphoid tissue fibrosis were associated with PIR ( 128 ).…”
Section: Plasma Markersmentioning
confidence: 99%
“…Corresponding to them were immunological responders (IRs), these patients achieved both virologic suppression and CD4+ T-cell count return to normal value. Since INR would increase the morbidity and mortality of AIDS-defining diseases (AD) and non-AIDS-defined diseases (NAD), research on INR had become the focus of current HIV-related research, and the relevant contents included the definition [2,3], mechanism [4,5] and treatment plans [6] guidelines [8] and understanding of INR by using similar indicators or adjacent time. For example, when a patient came to see a doctor on the 13th month and 12 days after receiving ART, the CD4+ T-cell count absolute number and the conversion rate at the 12th month in the guideline were generally used to determine whether the patient was INRs.…”
Section: Introductionmentioning
confidence: 99%